STUDI KARAKTERISTIK NILAI ROLLING RESISTANCE PADA PRODUK SINGLE ROW DEEP GROOVE BALL BEARING TIPE 6000 - Prakoso, Muhammad Ihsan; Jatisukamto, Gaguk; Darsin, Mahros; Asrofi, M; Triono, Agus (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
Rolling resistance in bearings is rolling resistance in bearings that move rolling without sliding. The amount of rolling resistance force occurs depending on the magnitude of the coefficient of friction between the ball bearing and the outer and inner surfaces of the bearing. This research is in the form of testing the characteristics of rolling resistance values by experimental methods when given variations in rotational speed parameters and radial load variations. The results of research on single row deep groove ball bearing type 6000 with 207 Newton loading at 300 rpm rotation showed a rolling resistance value of 1.0823 Newton.